2015
DOI: 10.1159/000370244
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Synergism of Gabapentin and Nortriptyline in Mice with Partial Sciatic Nerve Ligation

Abstract: Background and Methods: Neuropathic pain results from nerve injury, and gabapentin, an antiepileptic drug, has been approved for the treatment of several types of neuropathic pain. On the other hand, nortriptyline, an antidepressant drug, has been suggested as an alternative treatment. In partial sciatic nerve ligation (PSNL) mice, the interaction of gabapentin with nortriptyline was evaluated by the hot plate assay using isobolographic analysis. Results: Gabapentin (3-100 mg/kg, i.p.) or nortriptyline (1-30 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Six to eight mice were used in each GBT group (3, 30, and 100 mg/kg, i.p.) [ 42 43 ]. In the control group, four mice received the same volume of PBS, intraperitoneally.…”
Section: Methodsmentioning
confidence: 99%
“…Six to eight mice were used in each GBT group (3, 30, and 100 mg/kg, i.p.) [ 42 43 ]. In the control group, four mice received the same volume of PBS, intraperitoneally.…”
Section: Methodsmentioning
confidence: 99%
“…As it rapidly appeared that, under acute treatment conditions, agomelatine was ineffective on its own, we investigated whether it could develop anti-allodynic effects when combined with an anticonvulsant, namely gabapentin. Indeed, an abundant literature has shown that combined treatments with an antidepressant and an anticonvulsant most often produce synergistic effects, with much better alleviation of neuropathic pain than that expected from the sum of the effects expected from each drug alone ( Tomic et al, 2010 ; Miyazaki and Yamamoto, 2012 ; Gilron et al, 2013 ; Miranda et al, 2015 ). In both CCI-SN and CCI-ION rats, we found here that although gabapentin was administered at a dose, 50 mg/kg i.p., which produces no sedative effect and only minor, or even no, anti-allodynic effect ( Christensen et al, 2001 ; Patel et al, 2001 ; De Vry et al, 2004 ; Vanelderen et al, 2013 ), co-treatment with agomelatine + gabapentin effectively produced marked anti-allodynic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Gabapentin injected intradermally into the hindpaw can induce analgesia [Todorovic et al, ] and gabapentin is also effective in acute and chronic models of inflammatory pain [Singh et al, ; Heughan and Sawynok et al, ; Hurley et al, ] and reverses allodynia and hyperalgesia induced by 1% formalin [Salinas‐Abarca et al, ]. Gabapentin can decrease allodynia induced by nerve lesions in a neuropathic rat model [Chen et al, ; Field et al, ; Mixcoatl‐Zecuatl et al, ; Yamama et al, ; Miranda et al, ; Corona‐Ramos et al, ; Espinosa‐Juárez et al, ]. The antiallodynic effect of gabapentin may result from binding to the α2δ1 subunit of L‐type voltage‐dependent Ca 2+ channels [Gee et al, ] although it could activate other targets.…”
Section: Discussionmentioning
confidence: 99%
“…However, gabapentin has been co‐administered with (1) NSAIDs like naproxen [Hurley et al, ], meloxicam [Espinosa‐Juárez et al, ], ibuprofen [Yoon and Yaksh, ], diclofenac [Picazo et al, ] and metamizol [Ortega‐Varela et al, ]. (2) antidepressants like venlafaxine [Rode et al, ], nortriptyline [Miranda et al, ], and amitriptyline [Heughan and Sawynok, ]. (3) The opioids morphine [Shimoyama et al, ; De la O‐Arciniaga et al, 2009) and tramadol [Granados‐Soto and Argüelles, ].…”
Section: Discussionmentioning
confidence: 99%